2018
DOI: 10.3390/ijerph15081617
|View full text |Cite
|
Sign up to set email alerts
|

Changing Neighborhoods and Residents’ Health Perceptions: The Heart Healthy Hoods Qualitative Study

Abstract: Cities, and therefore neighborhoods, are under constant change. Neighborhood changes may affect residents’ health in multiple ways. The Heart Healthy Hoods (HHH) project studies the association between neighborhood and residents’ health. Focusing on a middle–low-socioeconomic neighborhood in Madrid (Spain), our aim was to describe qualitatively its residents’ perceptions on the urban changes and their impacts on health. We designed a qualitative study using 16 semi-structured interviews including adult residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…In the present study, indicators of subjective urban vulnerability were related to nonadherence. Two recent qualitative studies concluded that neighborhoods affect the health of residents by creating a social context that directly influences their beliefs and behaviors, such as adherence to prescribed treatment [39,40]. The fact that in our study nonadherence was associated with urban vulnerability and not with social class or income level could be because people in this age range have more homogenous salaries coming from their pensions despite living in communities with varying social statuses.…”
Section: Strengths and Comparison With Other Studiesmentioning
confidence: 51%
“…In the present study, indicators of subjective urban vulnerability were related to nonadherence. Two recent qualitative studies concluded that neighborhoods affect the health of residents by creating a social context that directly influences their beliefs and behaviors, such as adherence to prescribed treatment [39,40]. The fact that in our study nonadherence was associated with urban vulnerability and not with social class or income level could be because people in this age range have more homogenous salaries coming from their pensions despite living in communities with varying social statuses.…”
Section: Strengths and Comparison With Other Studiesmentioning
confidence: 51%
“…As a coping mechanism to the new form of social desirability, the slum migrants accept the social structure (rules and resources) encircling them, while constantly modifying some of this urban context with their practices (Giddens ). Hence, the co‐existence of traditional collectivism with emerging individualism in the same neighbourhood (Pedersen and Rytter ) with different health effects (Conde et al …”
Section: Introductionmentioning
confidence: 99%
“…This differential gap has not been the direct outcome of an age difference, but is due to an idea of stability and continuity of relationships between elders. As a result, building trusting relationships with the younger residents is unlikely, especially compared to relationships with "lifelong neighbors" (Conde et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moderate exercise is essential for successful aging (Lee et al 2012). However, the amount and diversity of physical activities can be limited by available infrastructure in the neighborhood (Bauman et al 2012;Conde et al 2018). In this regard, almost all residents of Neighborhood B walk through the neighborhood or its surroundings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation